Combined subcutaneous administration of ivermectin and nitroxynil in sheep: Age/body weight related changes to the kinetic disposition of both compounds - Moreno, Laura Susana (2010)
The effect of age/body weight in the plasma disposition kinetics of ivermectin (IVM) and nitroxynil (NTX) after their co-administration as a combined formulation to sheep was studied. Sixteen (16) male sheep were allocated into two experimental groups (n = 8 each): (a) high body weight (high bw) (18-20 months old), and (b) low body weight (low bw) (6-8 months old). Animals in both groups were subcutaneously (sc) treated with IVM (200 μg/kg) and NTX (10 mg/kg) using a commercially available combined formulation (Nitromectin®, Lab. Ovejero, Spain). Blood samples were taken by jugular venopuncture before (time 0), at 2, 4, 8, 12 h and at 1, 2, 3, 5, 7, 10, 15, 20, 25, 35, 40, 50 and 60 days after administration. Recovered plasma was analysed to quantify IVM and NTX by HPLC. Higher IVM plasma concentrations were measured until 20 days post-administration in "low bw" compared to "high bw" animals, where IVM was recovered up to 35 days post-treatment. The IVM absorption process greatly differed between experimental groups. A significantly higher (p < 0.01) Cmax (36.7 ± 7.52 ng/ml) value was obtained at a delayed (p < 0.05) Tmax (48.0 ± 0.0 h) in light compared to heavy (Cmax: 8.0 ± 0.80 ng/ml; at 34.0 h) body weight sheep. IVM elimination half-life and mean residence time were significantly shorter in light compared to heavy (older) sheep. NTX mean plasma concentrations were lower in "low bw" compared to those measured in "high bw" sheep, with elimination phases declining up to 60 d post-administration in both experimental groups. The NTX AUC value in "low bw" (1188.5 ± 122.6 μg day/ml) was significantly lower (p < 0.05) than that obtained in the "high bw" (oldest) animals (1735.0 ± 155.8 μg day/ml). Shorter NTX elimination half-life and mean residence time (p < 0.01) were obtained in the youngest ("low bw") compared to the oldest (high bw) sheep. The work reported here assessed for the first time the disposition of IVM and NTX after their combinated injection to sheep, demonstrating that animal body weight/development greatly affects the kinetic behaviour of both anthelmintic drugs.